ANGPTL4: A Predictive Marker for Diabetic Nephropathy - Eman Al Shawaf; Mohamed Abu-Farha; Sriraman Devarajan; Zahra Alsairafi; Irina Al-Khairi; Preethi Cherian; Hamad Ali; Aditi Mathur; Fahd Al-Mulla; Abdulnabi Al Attar; Jehad Abubaker (Journal of Diabetes Research)
Background. ANGPTL4 is a glycoprotein that is involved in regulating triglyceride metabolism by inhibiting LPL activity under fasting conditions. Additionally, ANGPTL4 has been suggested as a link between hypertriglyceridemia and albuminuria in the nephrotic syndrome. In this study, we examined levels of circulating ANGPTL4 in people with diabetic nephropathy (DN) and its association with established DN-associated proteins such as IGFBP1 and IGFBP4. Methods. We quantified circulating ANGPTL4, IGFBP1, IGFBP3, and IGFBP4 in fasting plasma samples of 122 Kuwaiti participants using a multiplexing assay. The study involved 36 controls, as well as 86 people with type 2 diabetes (T2D) including 37 people with normal kidney function and 49 people with DN. Results. ANGPTL4 level was increased in people with DN (241.56±14.1 μg/ml) compared to the control group (178.43±24.09 μg/ml). The increase in ANGPTL4 correlated with clinical parameters of DN including albumin-to-creatinine ratio (r=0.271, P=0.002), serum creatinine (r=0.381, P=0.0001), and eGFR (r=−0.349, P<0.0001). Furthermore, ANGPTL4 correlated positively with both IGFBP1 (r=0.202, P=0.026) and IGFBP4 (r=0.364, P<0.0001). Multiple regression analysis showed increased IGFBP1 and TG as predictors of higher ANGPTL4 in people with DN. In people with T2D, only IGFBP1 acted as a positive predictor of a rise in ANGPTL4. Conclusion. In this study, our data showed a significant increase in circulating ANGPTL4, IGFBP1, and IGFBP4 in patients with DN. The elevation in ANGPTL4 correlated significantly with clinical markers of DN such as ACR, serum creatinine, and eGFR, as well as IGFBP1 and IGFBP4. Altogether, this suggests a potential role for ANGPTL4 in DN perhaps through its role in inhibiting LPL activity and promotes ANGPTL4 as a biochemical marker for the detection of a diabetic kidney disease in patients with T2D.